2004
DOI: 10.1007/s11064-004-7036-0
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of A?(1?40) with Glycerophosphocholine and Intact Erythrocyte Membranes: Fluorescence and Circular Dichroism Studies

Abstract: Deposition of amyloid beta peptide in human brain in the form of senile plaques is a neuropathological hallmark of Alzheimer's disease (AD). Levels of a phospholipid breakdown product, glycerophosphocholine (GPC), also increase in AD brain. The effect of GPC on amyloid beta(1-40) peptide (Abeta) aggregation in PBS buffer was investigated by circular dichroism and fluoresence spectroscopy; interactions of Abeta and GPC with the intact erythrocyte membrane was examined by fluoresence spectroscopy. Fluorescamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This was observed using intact erythrocyte membranes. Glycerophosphocholine, a breakdown product of phospholipids, itself increased in AD individuals, was shown to enhance the aggregation of Ab in the erythrocyte membranes (Mandal et al, 2004). That lipid rafts may be important sites for not only cleavage of APP into Ab and Ab interactions with membrane lipids, Kawarabayashi et al (2004) reported the possible role of rafts in the formation of neurofibrillary tangles (NFTs).…”
Section: Lipid Modulation Of Amyloid Beta Aggregation and Neurotoxicitymentioning
confidence: 99%
“…This was observed using intact erythrocyte membranes. Glycerophosphocholine, a breakdown product of phospholipids, itself increased in AD individuals, was shown to enhance the aggregation of Ab in the erythrocyte membranes (Mandal et al, 2004). That lipid rafts may be important sites for not only cleavage of APP into Ab and Ab interactions with membrane lipids, Kawarabayashi et al (2004) reported the possible role of rafts in the formation of neurofibrillary tangles (NFTs).…”
Section: Lipid Modulation Of Amyloid Beta Aggregation and Neurotoxicitymentioning
confidence: 99%